2003
DOI: 10.1103/physreve.68.066307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electromagnetic boundary conditions onto the onset of dynamo action in laboratory experiments

Abstract: We study the onset of dynamo action of the Riga and Karlsruhe experiments with the addition of an external wall, the electro-magnetic properties of which being different from those of the fluid in motion. We consider a wall of different thickness, conductivity and permeability. We also consider the case of a ferro-fluid in motion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
39
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 11 publications
13
39
0
Order By: Relevance
“…Using boundary conditions with a high permeability in order to change the dynamo threshold has been already proposed [18]. It has been also shown that in the case of a Ponomarenko or G. O. Roberts flows, the addition of an external wall of high permeability can decrease the dynamo threshold [19]. Finally, recent kinematic simulations of the VKS mean flow have shown that different ways of taking into account the sodium behind the disks lead to an increase of the dynamo threshold ranging from 12 % to 150 % [20].…”
mentioning
confidence: 99%
“…Using boundary conditions with a high permeability in order to change the dynamo threshold has been already proposed [18]. It has been also shown that in the case of a Ponomarenko or G. O. Roberts flows, the addition of an external wall of high permeability can decrease the dynamo threshold [19]. Finally, recent kinematic simulations of the VKS mean flow have shown that different ways of taking into account the sodium behind the disks lead to an increase of the dynamo threshold ranging from 12 % to 150 % [20].…”
mentioning
confidence: 99%
“…Using boundary conditions with a high permeability in order to change the dynamo threshold has been already proposed [18]. It has been also shown that in the case of a Ponomarenko or G. O. Roberts flows, the addition of an external wall of high permeability can decrease the dynamo threshold [19]. Kinematic simulations of the VKS mean flow have shown that different ways of taking into account the sodium behind the disks lead to an increase of the dynamo threshold ranging from 12 % to 150 % [20].…”
Section: Impellersmentioning
confidence: 99%
“…In the other hand, in case (ii) the magnetic generation being within the fluid, a conducting external medium is not necessary for dynamo action, thus we choose an isolating external medium. Though the choice of the conductivity of the external medium is far from being insignificant for a dynamo experiment [3,4,6,7], we expect that it does not change the overall meaning of the results given below.…”
Section: Modelmentioning
confidence: 99%
“…In addition to the parameters usually considered, like the geometry of the mean flow [4,5] or the magnetic boundary conditions [6,7], the turbulent fluctuations of the flow seem to have an important influence on the dynamo threshold [8,9,10,11]. Some recent experimental results [12,13] suggest that the large spatial scales of these fluctuations could play a decisive role.…”
Section: Introductionmentioning
confidence: 99%